T cell perturbations persist for at least 6 months following hospitalization for COVID-19 - Govender, Melissa; Hopkins, Francis R.; Göransson, Robin; Svanberg, Cecilia; Shankar, Esaki M.; Hjorth, Maria; Nilsdotter-Augustinsson, Åsa; Sjöwall, Johanna; Nyström, Sofia; Larsson, Marie (Frontiers in Immunology, 2022)
COVID-19 is being extensively studied, and much remains unknown regarding the long-term consequences of the disease on immune cells. The different arms of the immune system are interlinked, with humoral responses and the production of high-affinity antibodies being largely dependent on T cell immunity. Here, we longitudinally explored the effect COVID-19 has on T cell populations and the virus-specific T cells, as well as neutralizing antibody responses, for 6-7 months following hospitalization. The CD8+ TEMRA and exhausted CD57+CD8+ T cells were markedly affected with elevated levels that lasted long into convalescence. Further, markers associated with T-cell activation were upregulated at the inclusion, and in the case of CD69+CD4+ T cells this lasted all through the study duration. The levels of T cells expressing negative immune checkpoint molecules were increased in COVID-19 patients and sustained for a prolonged duration following recovery. Within 2-3 weeks after symptom onset, all COVID-19 patients developed anti-nucleocapsid IgG and spike-neutralizing IgG as well as SARS-CoV-2-specific T cell responses. In addition, we found alterations in follicular T helper (TFH) cell populations, such as enhanced TFH-TH2 following recovery from COVID-19. Our study revealed significant and long-term alterations in T cell populations and key events associated with COVID-19 pathogenesis.